Das höhere Schulwesen der Stadt Königsberg in Preußen 1800 bis 1915 - Hinz, Margund (Quellen und Forschungen zur Brandenburgischen und Preußischen Geschichte, 2020)
»The Higher Education System of the City of Königsberg in Prussia 1800 to 1915«: The study is the first to present the secondary school system of the capital and royal seat Königsberg in Prussia in the period from 1800 to 1915 - against the background of striking supraregional events affecting the entire state of Prussia. The author explores the regional characteristics of the ›Gymnasien‹ as well as the development of the ›Realanstalten‹ and the higher education of girls. Among the eight schools included, the ›Königliches Friedrichs-Kollegium‹ occupies a prominent position because of its model character for all of Prussia. Wilhelm von Humboldt's activities in Königsberg, which were fundamental for the school reform from 1809 onwards, and the Königsberg school plan he developed there are dealt with in detail by the author. In accordance with Humboldt's goal of equal status for the subjects Latin and Greek, mathematics and history, these and the corresponding teaching subjects as well as research at Königsberg University are considered in detail. A separate chapter is devoted to the reception of Humboldt's school concept in the Baltic provinces.